Ultrasonics absorption measurements of a liquid with backed transducer - BINDAL, V. N.; SAKSENA, T. K.; SOM, J. N. (Archives of Acoustics, 1986)
An effect of backing of the transducer on the measured value of absorption of a liquid have been shown using shock excited system. The resulting deviation in the measured value of absorption from the accepted value has been observed to be large as 40 %, depending on the damping produced. A mechanism to explain the observed variation of the measured value of absorption with backing has been put forward. Implication of the work in characterisation of ultrasonic probe have been discussed.